Multi-faceted approaches toward unravelling complex ecological networks - Namba, Toshiyuki (Population ecology, 2015)
The main theme of this Special Feature is the complexity-stability relationship and diversity of interaction types. Five articles by leading authors are submitted. Studies on the relationship between complexity and stability have a long history of 40 years. Effect of multiple interaction types on structure and dynamics of an ecological network is a recent important subject to be resolved. In this preface, I briefly review the history of research on complexity-stability relationship till the idea of diversity of interaction types appears.